TALQIN MAYIT ANALISIS KUALIFIKASI HADITH DALAM KITAB SUNAN ABU DAWUD - Arofik, Slamet (UNIVERSUM : Jurnal KeIslaman dan Kebudayaan, 2017)
Hadith is not only as the second source of Islamic law after al-Qur’an, but also as the model in organizing human life in both social and spiritual practice. However, the hadith historiography mentions that there is some Muslim communities that doubt the function and legality of those second source of Islamic law. One case that is still debated according to them is the hadith qualification about talqin stated in Sunan Abu Dawud book no. Index 2710. This study is library research that aims at researching and explaining the qualification of sanad and matan of hadith talqin mayit stated in Sunan Abu Dawud book, and how is the hujjah of the hadith, and what is the meaning of talqin word in those hadith. The research finding shows that based on sanad side the hadith is ahad hadith having shahih level. Since all critics value thiqoh in all linking (riwayah,) and there is no shudud and ’illat on it. Furthermore, from matan side, the hadith is also shahih since it has been fulfilled the shahih (validity) norms. Keywords: talqin, hadith qualification, matan, ṣahīh